KOI FISH AS AN INSPIRATION FOR WALL DECORATION ARTWORK - Rengga Kusuma Nawala Sari; Sri Wuryani; Kosalalita Anggiyumna R. (Institut Seni Indonesia Surakarta, 2022)
Koi fish breeding in Blitar City produces Koi with superior quality. Koi fish are also used as the mascot of this city. Koi fish from Blitar are widely marketed both nationally and internationally. This is inextricably linked to the shape and color attractiveness of koi fish. Accordingly, koi fish are an interesting source of inspiration for wall art creation. The creation of this ornamental artwork used an aesthetic approach. The three steps of the creative process were exploration, design, and embodiment. Tapestry and knitting techniques were used in the embodiment technique. This process produced three decorative artworks: (1) “Koi Fish Harmony”, which depicts a harmonious life; (2) “Meek Soft”, illustrates gentleness; and (3) “The King of Freshwater Fish”, which portrays charming luxury.